A multi-frequency analysis of possible dark matter contributions to M31 gamma-ray emissions. Issue 10 (6th October 2017) - Beck, G.; Colafrancesco, S.
Abstract: We examine the possibility of a dark matter (DM) contribution to the recently observed gamma-ray spectrum seen in the M31 galaxy. In particular, we apply limits on Weakly Interacting Massive Particle DM annihilation cross-sections derived from the Coma galaxy cluster and the Reticulum II dwarf galaxy to determine the maximal flux contribution by DM annihilation to both the M31 gamma-ray spectrum and that of the Milky-Way Galactic Centre. We limit the energy range between 1 and 12 GeV in M31 and Galactic Centre spectra due to the limited range of former's data, as well as to encompass the high-energy gamma-ray excess observed in the latter target. In so doing, we will make use of Fermi-LAT data for all mentioned targets, as well as diffuse radio data for the Coma cluster. The multi-target strategy using both Coma and Reticulum II to derive cross-section limits, as well as multi-frequency data, ensures that our results are robust against the various uncertainties inherent in modelling of indirect DM emissions. Our results indicate that, when a Navarro-Frenk-White (or shallower) radial density profile is assumed, severe constraints can be imposed upon the fraction of the M31 and Galactic Centre spectra that can be accounted for by DM, with the best limits arising from cross-section constraints from Coma radio data and Reticulum II gamma-ray limits. These particular limits force all the studied annihilation channels to contribute 1% or less to the total integrated gamma-ray flux within both M31 and Galactic Centre targets. In contrast, considerably more, 10−100 %, of the flux can be attributed to DM when a contracted Navarro-Frenk-White profile is assumed. This demonstrates how sensitive DM contributions to gamma-ray emissions are to the possibility of cored profiles in galaxies. The only channel consistently excluded for all targets and profiles (except for ∼ 10 GeV WIMPs) is the direct annihilation into photons. Finally, we discuss the ramifications of evidence in favour of cored halo density profiles for DM explanations of galactic gamma-ray emission.